(untitled) (Libya Journal of Geographical Studies, 2026)
The use of deviation-from-mean data is useful for identifying the onset and termination of meteorological drought. However, agricultural drought, hydrological drought, and water management drought do not end immediately following above-average rainfall. This is because previous drought years leave the soil extremely dry, absorbing most of the precipitation, with a significant portion lost to evaporation, leaving only a limited amount for surface and groundwater storage. The rainfall record in Tripoli from 1959 to 1998 included 22 drought years, of which 8 were isolated, 4 were consecutive pairs, and one was an extended period of six consecutive years. Examination of the data (Table 1, column 4) indicates that the 1980/81–1981/82 drought was the most severe, with an annual deficit of 154.7 mm, followed by 1996/97 with 151.8 mm. The severity of any drought period is determined not only by the annual deficit but also by its duration. Accordingly, the 1989–1994 drought, although ranked fourth in terms of annual deficit, caused the greatest impact on agricultural, pastoral, and water resources due to its six-year duration, accumulating a total deficit of 30.95% of all deficits recorded in the area since 1959. This was followed by the 1980–81 drought (15.75%) and the 1967–68 drought (10.69%(. Cumulative analysis also indicated that the study area experienced two prolonged hydrological drought periods: the first from 1961 to 1970, interrupted by three above-average rainfall years (1963, 1966, and 1969), and the second from 1989 to 1998, interrupted by two above-average rainfall years (1995 and 1997). The wet period from 1971 to 1979 was only interrupted by the 1976 drought.